Oral Bromelain Attenuates Inflammation in an Ovalbumin-Induced Murine Model of Asthma. Issue 1 (2008) - Secor, Eric R.; Carson, William F.; Singh, Anurag; Pensa, Mellisa; Guernsey, Linda A.; Schramm, Craig M.; Thrall, Roger S.
Abstract : Bromelain, a widely used pineapple extract with cysteine protease activity, has been shown to have immunomodulatory effects in a variety of immune system models. The purpose of the present study was to determine the effects of orally administered bromelain in an ovalbumin (OVA)-induced murine model of acute allergic airway disease (AAD). To establish AAD, female C57BL/6J mice were sensitized with intraperitoneal (i.p.) OVA/alum and then challenged with OVA aerosols for 3 days. Mice were gavaged with either (phosphate buffered saline)PBS or 200 mg/kg bromelain in PBS, twice daily for four consecutive days, beginning 1 day prior to OVA aerosol challenge. Airway reactivity and methacholine sensitivity, bronchoalveolar lavage (BAL) cellular differential, Th2 cytokines IL-5 and IL-13, and lung histology were compared between treatment groups. Oral bromelain-treatment of AAD mice demonstrated therapeutic efficacy as evidenced by decreased methacholine sensitivity ( P ≤ 0.01), reduction in BAL eosinophils ( P ≤ 0.02) and IL-13 concentrations ( P ≤ 0.04) as compared with PBS controls. In addition, oral bromelain significantly reduced BAL CD19+ B cells ( P ≤ 0.0001) and CD8+ T cells ( P ≤ 0.0001) in AAD mice when compared with controls. These results suggest that oral treatment with bromelain had a beneficial therapeutic effect in this murine model of asthma and bromelain may also be effective in human conditions.